The Philosophical Significance of the Naber Laut Tradition in Shaping the Cultural Identity of Batu Beriga Village (1963–2018) - Heryati Heryati; Yusinta Tiarusdiana; Juita Mahardika (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
This study explores the philosophical significance embedded in the Naber Laut tradition practiced by the community of Batu Beriga Village, Central Bangka Regency, from 1963 to 2018. The Naber Laut tradition is a customary ceremony rooted in animistic and dynamistic beliefs, serving as an expression of gratitude for the bounty of the sea as well as a plea for the safety of fishermen. This research employs historical methods with a qualitative descriptive approach, utilizing interviews, observations, and documentation techniques. The findings indicate that this tradition embodies spiritual, social, and cultural values that strengthen local identity and serve as a form of resistance against the tide of modernization. The Naber Laut tradition also represents the harmonious relationship between humans and nature, passed down through generations. This study’s findings strengthen efforts to preserve local culture amidst the dynamics of social change. This study sheds new light on how local traditions function as dynamic cultural adaptation strategies in the face of modernization.